2017
DOI: 10.1371/journal.pone.0180105
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Corynebacterium diphtheriae macrophage interaction: Dispensability of corynomycolic acids for inhibition of phagolysosome maturation and identification of a new gene involved in synthesis of the corynomycolic acid layer

Abstract: Corynebacterium diphtheriae is the causative agent of diphtheria, a toxin mediated disease of upper respiratory tract, which can be fatal. As a member of the CMNR group, C. diphtheriae is closely related to members of the genera Mycobacterium, Nocardia and Rhodococcus. Almost all members of these genera comprise an outer membrane layer of mycolic acids, which is assumed to influence host-pathogen interactions. In this study, three different C. diphtheriae strains were investigated in respect to their interacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 72 publications
2
17
0
Order By: Relevance
“…In summary, the different non-toxigenic C. diphtheriae isolates were able to persist longer periods within the BMM compared to C. glutamicum and toxigenic DSM43989, and were partially able to proliferate within the first 4 h post-infection. This result indicated that C. diphtheriae is able to cause a delay of phagolysosome maturation in macrophages, which was shown in a previous study for different C. diphtheriae strains [13].…”
Section: Survival Of C Diphtheriae After Internalization By Primary supporting
confidence: 85%
See 2 more Smart Citations
“…In summary, the different non-toxigenic C. diphtheriae isolates were able to persist longer periods within the BMM compared to C. glutamicum and toxigenic DSM43989, and were partially able to proliferate within the first 4 h post-infection. This result indicated that C. diphtheriae is able to cause a delay of phagolysosome maturation in macrophages, which was shown in a previous study for different C. diphtheriae strains [13].…”
Section: Survival Of C Diphtheriae After Internalization By Primary supporting
confidence: 85%
“…In all infection studies that have been made thus far with different C. diphtheriae wild type strains and epithelial cells [20] or human and murine macrophages in this study, the toxigenic strain DSM43989 was not able to adhere to or to invade into the host cells and it was obviously not taken up in macrophages. Additionally, former studies demonstrated that this strain does not contain mycolic acids in its cell wall [13]. In this study, it was shown that DSM43989 induces inflammatory response in the host as well as host cell damage.…”
Section: Influence Of the Diphtheria Toxinmentioning
confidence: 68%
See 1 more Smart Citation
“…2. Some molecules were seen in both strains, such as the ones presenting estimated molecular weights of 76, 66, 54, 45,37,34,31,29,21,17,15, and 14 kDa. However, some differences were observed between the two strains.…”
Section: Resultsmentioning
confidence: 99%
“…These molecules, which have been reported to enhance bacterial survival inside macrophages and dendritic cells [42], inhibit the production of pro-inflammatory cytokines such as interleukin-12 (IL-12) and tumor necrosis factor (TNF) and impair phagosome maturation [43,44]. Unexpectedly, however, a mycolic acid-free mutant of C. diphtheriae was still able to delay phagolysosome formation in murine and human macrophage cell lines and showed no virulence differences to mycolic acid containing strains [45], indicating that at least in this species, mycolic acids do not interfere with macrophage maturation. Therefore, it c a n b e s u g g e s t e d t h a t t h e m a r k e d a m o u n t o f glycerophosphoinositols only found in the VD57 C. pseudotuberculosis strain, as shown by the MS results, may be related to an impaired immune response activation, leading to an increased potential in causing severe CLA.…”
Section: Discussionmentioning
confidence: 99%